Quantitative and qualitative analysis of quality of life in people diagnosed with genetic haemochromatosis in the United Kingdom - Leah Craven-Smith; Neil McClements; Diogo Gomes; Victoria Pointon (Journal of Patient-Reported Outcomes)
Abstract Background Genetic haemochromatosis (GH) is a long-term genetic condition which results in increased iron absorption into the blood and accumulation of iron into certain organs overtime. Increased absorption and accumulation can be fatal. GH can cause many symptoms including arthritis/joint pain, chronic fatigue, and cognitive difficulties. The aim of this study was to measure quality of life (QoL) in people diagnosed with GH (GH-diagnosed) compared to a healthy sample and identify possible explanations for this. Methodology QoL was measured in 535 healthy people and 1039 GH-diagnosed, through completion of the World Health Organisation Quality of Life-100 survey (WHOQOL-100). 985 GH-diagnosed respondents completed a GH-focussed survey, which was developed to get further details of the impact of GH. Results Comparison of the WHOQOL-100 overall QoL score between GH-diagnosed and the healthy sample found a significantly lower score in the GH-diagnosed. Physical, psychological, level of independence, and spiritual domains were significantly lower in the GH-diagnosed group. The GH-focussed survey found a high incidence of physical and mental symptoms, and some impact on social and work life. Areas in which participants suggest would improve their QoL included: improved healthcare especially with increased understanding of GH in medical professionals, increased access to appointments, in-person appointments, regular checks for organ damage, more nutrition or dietary advice, and local support groups. Conclusions Based on the WHOQOL-100 scores and GH-focussed survey, overall QoL is worse in people diagnosed with GH due to worse physical and psychological symptoms. Improved healthcare may aid in reducing the difference in QoL.